2012
DOI: 10.1371/journal.pone.0052856
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy Outcomes among Adolescents and Youth in Rural Zimbabwe

Abstract: Around 2 million adolescents and 3 million youth are estimated to be living with HIV worldwide. Antiretroviral outcomes for this group appear to be worse compared to adults. We report antiretroviral therapy outcomes from a rural setting in Zimbabwe among patients aged 10–30 years who were initiated on ART between 2005 and 2008. The cohort was stratified into four age groups: 10–15 (young adolescents) 15.1–19 years (adolescents), 19.1–24 years (young adults) and 24.1–29.9 years (older adults). Survival analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
87
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 15 publications
7
87
2
Order By: Relevance
“…Moreover, facilities reported insufficient protocols for determining and managing both non‐adherence and LTFU, as well as limited use of counselling tools to inform their interventions. This is problematic as research indicates that adolescents and young people are at high risk of LTFU, especially those aged 15–19 years [7,8,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, facilities reported insufficient protocols for determining and managing both non‐adherence and LTFU, as well as limited use of counselling tools to inform their interventions. This is problematic as research indicates that adolescents and young people are at high risk of LTFU, especially those aged 15–19 years [7,8,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown that adolescents have worse adherence compared to adults and younger children [8, 9]. Adolescents are the only group for which AIDS-related mortality has not decreased [10, 11] with AIDS being the leading cause of adolescent death in sub-Saharan Africa [12]. …”
Section: Introductionmentioning
confidence: 99%
“…As noted by other researchers, approaches by providers and school administrators that may help to improve engagement in care and warrant further study include having open conversations and acknowledging challenges faced by adolescents in adhering to their drug regimen, and working together to identify solutions (Bernays, Paparini, Gibb, & Seeley, 2016; Denison et al, 2015). Additionally, development of new drug formulations that are long-acting, more tolerable and less burdensome (e.g., smaller tablets, chewable or liquid alternatives, once-a-day pills) may make a significant contribution toward improving engagement in care for adolescents living with HIV in resource-poor settings with limited clean water availability (Adejumo, Malee, Ryscavage, Hunter, & Taiwo, 2015; Bygrave et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescent HIV testing in Kenya is well below the World Health Organization 90% target at 35% and 27% among females and males aged 15–19, respectively (UNICEF, 2016). Additionally, a growing number of studies in southern and eastern sub-Saharan countries have found that youth ages 15–24 years are less likely to enrol in care after HIV diagnosis and more likely to be lost to care after enrolment compared to either older or younger groups (Auld et al, 2014; Bygrave et al, 2012; Evans et al, 2013; Genberg et al, 2015; Hatcher et al, 2012; Koech et al, 2014; Lamb et al, 2014; Naik et al, 2015). They are also less likely than adults to adhere to ART after initiation and subsequently experience shorter time to viral rebound and lower rates of virological suppression and immunological recovery (Nachega et al, 2009).…”
Section: Introductionmentioning
confidence: 99%